Agile leadership and its relationship to crisis management among the heads of scientific departments at King Abdulaziz University from the point of view of faculty members - Abdulaziz Alharazi (Umm Al-Qura University, 2022)
The study aimed to identify the relationship between agile leadership and crisis management among the heads of scientific departments at King Abdulaziz University from the point of view of the faculty members. The study used the descriptive correlative method, and the study sample consisted of (359) members, The questionnaire was the tool used to collect study data. The study reached a number of results, the most prominent of which were: The dimensions of agile leadership among the heads of scientific departments at the university are generally available at a medium degree, with the average approval of the study sample members on the degree of availability of all these dimensions (3.19), And that the heads of scientific departments at the university practice crisis management operations to a medium degree in general, with an average of (3.13), and the results of the study revealed positive relationship with statistical significance between the degree of availability of dimensions of agile leadership and the level of crisis management practice among the heads of scientific departments, as all The values ​​of Pearson correlation coefficients are positive and function at the significance level (0.01), The results also revealed that there were no statistically significant differences in the responses of the study sample to the difference of the type of college and gender. The study recommended a number of recommendations, the most important of which are: The necessity of working to provide the necessary training programs for heads of scientific departments that contribute to increasing the level of awareness of the importance of agile leadership practices and their role in addressing and managing crises, Contribute to providing the necessary requirements to achieve the practices of agile leadership in a way that achieves its objectives in the academic work, adopting the necessary material and moral stimulus programs for the heads of scientific departments, which contributes to increasing their motivation towards agile leadership practices and its role in crisis management.